Pneumocystis jirovecii Pneumonia in Patients with Nephrotic Syndrome: Application of Lymphocyte Subset Analysis in Predicting Clinical Outcomes - Yang Liu; Ke Zheng; Yecheng Liu; Huadong Zhu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Purpose. With immunosuppressants being widely used, Pneumocystis jirovecii pneumonia (PCP) has been increasing and could be life-threatening among HIV-negative patients. This study aimed at identifying prognostic factors of PCP in patients with nephrotic syndrome. Methods. We retrospectively investigated patients with nephrotic syndrome who were diagnosed with PCP. The diagnosis of PCP was based on clinical manifestations, radiological findings, and microbiological confirmatory tests. Predictors of outcome were determined with multivariate logistic regression analysis. Results. A total of 57 patients were included in this study. The PCP mortality was 33.3%, which increased to 48.6% if ICU admission was required and to 60% when mechanical ventilation was needed. The T lymphocyte count and CD4/CD8 ratio independently predicted the outcome of PCP, so did the CD4+ T lymphocyte count (OR, 0.981; 95% CI, 0.967–0.996; p=0.001). The cut-off value of 71 cells/μl for the CD4+ T lymphocyte count was determined to identify patients with poor prognosis. No association was found between PCP mortality and the type of immunosuppressant used. Conclusions. PCP is a fatal complication among nephrotic syndrome patients receiving immunosuppressive therapy. The CD4+ T lymphocyte count is suggested as an independent predictor of prognosis, which can be used clinically to identify patients with high risk of unfavorable outcomes.